Numerical Simulation of High Efficiency Environment Friendly CuBi2O4-Based Thin-Film Solar Cell Using SCAPS-1D - Kushal Sarker; Md. Shamsujjoha Sumon; Mst. Farzana Orthe; Sunirmal Kumar Biswas; Md. Mostak Ahmed (International Journal of Photoenergy)
In this research work, a copper bismuth oxide- (CuBi2O4-) based thin-film solar cell has been proposed for the lead and toxic-free (Al/ITO/TiO2/CuBi2O4/Mo) structure simulated in SCAPS-1D software. The main aim of this work to make an ecofriendly and highly efficient thin-film solar cell. The absorber layer CuBi2O4, buffer layer TiO2, and the electron transport layer (ETL) ITO have been used in this simulation. The performance of the suggested photovoltaic devices was quantitatively evaluated using variations in thickness such as absorber, buffer, defect density, operating temperature, back contact work function, series, shunt resistances, acceptor density, and donor density. The absorber layer thickness is fixed at 2.0 μm, the buffer layer at 0.05 μm, and the electron transport layer at 0.23 μm, respectively. The CuBi2O4 absorber layer produces a solar cell efficiency of 31.21%, an open-circuit voltage (Voc) of 1.36 V, short-circuit current density (Jsc) of 25.81 mA/cm2, and a fill factor (FF) of 88.77%, respectively. It is recommended that the proposed CuBi2O4-based structure can be used as a potential for thin-film solar cells that are both inexpensive and highly efficient.